The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1055/s-2007-1004888
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Demonstration of Putative Nuclear 3,5,3'-Triiodothyronine Receptors in Isolated Liver Nuclei of Singi Fish, Heteropneustes Fossilis (Bloch)

Abstract: Putative thyroid hormone (TH) receptors have been demonstrated in the isolated liver nuclei of Singi fish, Heteropneustes fossilis (Bloch), and their binding characteristics have been examined. Nuclear T3 saturation analyses were carried out in vitro at 27 degrees C in a sucrose-Tris-HCl buffer (pH 7.5) containing calcium (2 mM), magnesium (3 mM) and 2-mercaptoethanol (5 mM). After incubation the bound and free hormones were separated by centrifugation and the nuclei were treated with Triton X-100 (final conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Thyroid hormone elevates the level of FAA in the liver of gold fish, Carassius auratus (Thornburn and Matty 1963). Thyroxine being a vertebrate hormone is naturally responsible for various metabolic events in different vertebrates (Barsano and DeGroot 1983;De, Ray and Medda 1988;Dey, Dasmahapatra, Ray and Medda 1989;Dasmahapatra, Ray and Medda 1990). However, its involvement in silkworm life processes has created a new chapter to be explored concerning how this vertebrate hormone alone influences a number of metabolic processes in different organs of invertebrates without thyroid.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid hormone elevates the level of FAA in the liver of gold fish, Carassius auratus (Thornburn and Matty 1963). Thyroxine being a vertebrate hormone is naturally responsible for various metabolic events in different vertebrates (Barsano and DeGroot 1983;De, Ray and Medda 1988;Dey, Dasmahapatra, Ray and Medda 1989;Dasmahapatra, Ray and Medda 1990). However, its involvement in silkworm life processes has created a new chapter to be explored concerning how this vertebrate hormone alone influences a number of metabolic processes in different organs of invertebrates without thyroid.…”
Section: Discussionmentioning
confidence: 99%
“…Putative nuclear T3-binding receptors have been described in salmonids, the European eel and several catfish species for the liver (Van der Kraak and Eales, 1980;Darling et a/., 1982b;Bres and Eales, 1986;Chakraborti etal., 1986;Weirich etal., 1987;Ichikawa et al, 1989;Lebel and Leloup, 1989;Dasmahapatra et al, 1991a), gill (Bres and Eales, 1988;Lebel and Leloup, 1989), brain (Darling et al, 1982b;Bres and Eales, 1988;White et al, 1990;Dasmahapatra et al, 1991b), kidney (Bres and Eales, 1988), pituitary (Bres and Eales, 1989), erythrocytes (Sullivan et al, 1987;Bres and Eales, 1988), ovary (Chakraborti et al, 1986;Maitra and Bhattacharya, 1989), but could not be demonstrated in spleen (Darling et al, 1982b;Bres and Eales, 1988). The affinity (Kd) of receptors from these various tissues was approximately 10-9-10-1°M (determined in vitro), and the estimated number of receptors per nucleus ranged from about 10 (erythrocytes) to over 1000 (liver).…”
Section: Receptor Functionmentioning
confidence: 98%
“…GDH is localized mainly in the mitochondrial part of the cell (Harper et al, 1993). The results are supported by Hemavathi et al (2002) and Dasamahapatra et al (1990), who presented the amplified activity of glutamate dehydrogenase, had positive metabolic modulation leading to synthesis of more energy required to produce improved quality cocoons. The possible reason for the progressive increase in haemolymph glutamate dehydrogenase activity during fifth instar might be due to increasing energy demands for muscular activity for the formation of quality cocoon and for formation and mobility of sperms.…”
Section: Discussionmentioning
confidence: 51%